Maki Ishii und sein Engagement bei den Darmstädter Ferienkursen und dem Deutsch-Japanischen Festival für Neue Musik in Tokio - Caitano, Joevan de Mattos (Die Musikforschung, 2023)
This article examines the legacy of the Japanese composer Maki Ishii (1936–2003) based on his works and his activities in Berlin, Darmstadt, and Tokyo. Using hitherto unknown source material in the Archives of the Internationales Musikinstitut Darmstadt (IMD) and the Maki-Ishii-Archive in Berlin, the article demonstrates how Maki Ishii arrived at the Darmstädter Ferienkurse by presenting letters of reference by important people, as well as the reception of the events in Darmstadt in Tokyo through the interaction of this well-known composer with intercultural engagement. The relevance of the “Deutsch-Japanisches Festival für Neue Musik”, which was organized by Ishii and Yoshirō Irino in close collaboration with the directors of the Goethe Institute in Tokyo, is attested in the programmes collected at the Archives of Modern Japanese Music at the Meiji Gakuin University in Tokyo. The source-based approach explains Maki Ishii’s role in connecting Darmstadt with Japan and Japan with Darmstadt, and shows how he became one of the pioneers to internationalize traditional and modern Japanese music after the Second World War.